Pustakawan Islam dalam menghadapi era MEA - Wilantika Ramadhani (IQRA`: Jurnal Ilmu Perpustakaan dan Informasi (e-Journal), 2017)
This article discusses the readiness of Islamic librarians facing Asian economic community (MEA). As a professional, librarians must prepare themselves in the competition in the era of technology and especially to Islamic librarians, must be able to compete with other librarians by improving the ability in self and always based on the principles of Islamic teachings. Keywords: Islamic librarians, technology.